The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1155/2016/5923938
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Alterations in Peripheral Mononuclear Blood Cells from Alzheimer’s Disease and Mild Cognitive Impairment Patients

Abstract: It is well recognized that mitochondrial dysfunction contributes to neurodegeneration occurring in Alzheimer's disease (AD). However, evidences of mitochondrial defects in AD peripheral cells are still inconclusive. Here, some mitochondrial-encoded and nuclear-encoded proteins, involved in maintaining the correct mitochondria machine, were investigated in terms of protein expression and enzymatic activity in peripheral blood mononuclear cells (PBMCs) isolated from AD and Mild Cognitive Impairment (MCI) patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 57 publications
(56 reference statements)
0
45
0
Order By: Relevance
“…Consistent with our result, as reported by Delbarba et al, AD PBMCs show a significant decrease in PGC1α expression, while PCG1α was unchanged in mild cognitive impairment (MCI) patients. Additionally, the expression of TFAM dropped in PBMCs derived from both AD and MCI patients . In addition, to the best of our knowledge, this is the first study reporting alterations in PGC1α , and TFAM levels in peripheral cells of parkinsonian patients.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Consistent with our result, as reported by Delbarba et al, AD PBMCs show a significant decrease in PGC1α expression, while PCG1α was unchanged in mild cognitive impairment (MCI) patients. Additionally, the expression of TFAM dropped in PBMCs derived from both AD and MCI patients . In addition, to the best of our knowledge, this is the first study reporting alterations in PGC1α , and TFAM levels in peripheral cells of parkinsonian patients.…”
Section: Discussionmentioning
confidence: 61%
“…There is a substantial literature indicating possible links between PGC1α and diverse neurodegenerative diseases (NDDs), comprising amyotrophic lateral sclerosis (ALS), Huntington's disease (HD), Alzheimer's disease (AD) and PD . As a target gene of PGC1α, TFAM regulates mitochondrial genome replication and transcription as well as mitochondrial biogenesis . TFAM also makes a positive contribution to mtDNA stability and initiates synthesis of mtDNA‐encoded respiratory chain subunits .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many investigators have suggested that epigenetic changes in the copy numbers of mtDNA and mtDNA mutations might be involved in AD pathogenesis [60][61][62][63][64][65]. However, the analysis of the literature reveals the existence of inconsistent findings and methodological shortcomings affecting a large proportion of mtDNA association studies on AD [66][67][68][69].…”
Section: Mitochondrial Dysfunction In Admentioning
confidence: 99%
“…Moreover, it was seen that there is a tendency in the group of participants without AD since, when cortisol increases, there is a decrease in IgA in saliva, while in AD participants, when cortisol increases, the IgA level in saliva increases too. All of these changes can be explained due to cellular, molecular and physiological changes in the organism that are also related to the mood of patients [13][14][15].…”
Section: Immune System and Admentioning
confidence: 99%